Nazwy własne jako nośnik wartościowania i emocjonalności w listach Joachima Lelewela = Proper names as carriers of evaluation and emotionality in Joachim Lelewel's letters - Jaros, Violetta (Zielona Góra: Uniwersytet Zielonogórski, Instytut Filologii Polskiej)
The article's subject is related to the textual use of propria as carriers of evaluation and emotionality in Joachim Lelewel's letters addressed to relatives, friends and acquaintances. Explicit exponents of the emotive-expressive function are appropriately marked with word-formation formants and inflectional morphemes.
Keywords: nazwa własna; wartościowanie; emocjonalność; list; język potoczny; język familijny; proper name; evaluation; emotionality; letter; common language; family language